The Austrian insurance industry: A structure, conduct and performance analysis - Lorenz Jedlicka; Adusei Jumah (Institute for Advanced Studies (IHS), 2006)
There exist a vast number of studies on the banking industry. However, the insurance industry remains relatively unexplored. Increasingly, Austrian insurance institutions are becoming important as financial intermediaries in the domestic market, and - based on proximity advantage - also in the Central and Eastern European markets. This paper applies the structure, conduct and performance (SCP) approach to a sample of 52 Austrian insurance firms. The main finding is that the standard SCP hypothesis of highly concentrated markets, which create incentives to engage in collusive behaviour and which in turn leads to higher industry profit rates, cannot be supported by the Austrian insurance industry. leads to higher industry profit rates, cannot be supported by the Austrian insurance industry.
Keywords: G22; L1; 330; insurance industry; market structure; conduct and performance; industrial organisation; Versicherung; Marktstruktur; Branchenentwicklung; Struktur-Performance-Modell; Österreich